Penggunaan Media Gambar Rumah Adat Jawa Tengah Untuk Mengenalkan Bangun Datar pada Pembelajaran Matematika Siswa Kelas 2 - SETIYANI, YULI (Educreative : Jurnal Pendidikan Kreativitas Anak, 2020)
The use of learning media for traditional Javanese traditional houses in mathematics learning of flat-build material selected by teachers in class 2 MI MA'ARIF NU 2 SANGGREMAN results showed an increase in learning activities both in terms of activities and learning outcomes. This research is a case study research. The activity shows during the implementation of learning activities motivation, interest, activity, involvement, and enthusiasm of students to learn in the "high" category. Learning activities also take place interactively. Question and answer activities built by the teacher were welcomed by students. From the results of the implementation of Mathematics learning activities the material of flat build by utilizing the learning media of traditional houses in Central Java showed maximum results. From 12 students of grade 2, the number of students who have reached KKM is 10 students or 83.33% and not yet KKM is only 2 students or 16.67% students. And the classical average has reached the classical completeness which is 80.33.